Self-consciousness and social comparison of working students in selected food chains in Iloilo City. - Gigawin, Ma. Kristina R.; Parcon, Donabel Mae F. (2004.)
This study sought to know if there exists a relationship between self-conciousness and social comparison among sixty-two (62) college working students, both males and females enrolled in the second semester of Academic Year 2003-2004, in selected food chains in Iloilo City., Results indicted that there is a correlation between the self-consciousness and the tendency for social comparison among the respondents as computed (r = 0.3) using the Pearson-r Product Moment of coefficient Correlation. It was also found out that college working students are generally self-concious, predominantly in their private aspects, and although they engage in both directions of social comparison, they usually evaluate themselves on the basis of those others who perform better than them. Their socio-demographic characteristics have significant influences to their decision to work while in school. Gaining work experience is a major contribution to the factors as to why the students take part-time jobs.
Research Project (Undergraduate, Bachelor of Arts in Psychology-Sociology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Food Chains -- Iloilo City